The Terra Cotta Army : China's first emperor and the birth of a nation - Man, John, 1941- (Da Capo Press, 2009)
The terra cotta army is one of the greatest, and most famous, archaeological discoveries ever made. Over eight thousand life-size figures of warriors and horses were interred in the mausoleum of the first emperor of China--and each figure is individually carved, perhaps representing real members of the emperor's army. Weaving together history and a first-hand account of his experience in China, John Man tells the fascinating story of how and why these astonishing figures were created in the third century BC. In doing so, he gives a vivid account of early China and the formation of its unique culture.--From publisher description.